Modulation of slug flow characteristics observed in three-phase solid-liquid-gas flow measurements - Cavalli, Stella; Alves, Rafael F.; Lange Bassani, Carlos; Marcelino Neto, Moisés A.; Sum, Amadeu K.; Morales, Rigoberto E.M. (Chemical Engineering Science, 2024)
The formation and agglomeration of gas hydrates represent a critical issue in flow assurance. This research aims to evaluate the transport and impact of particles on the slug flow pattern. Experimental investigations were conducted using inert polyethylene particles, mimicking gas hydrates, with four different particle sizes (100 µm, 200 µm, 300 µm and 400 µm) and three volumetric concentrations (1 %, 2.5 % and 5 %) with air and water as working fluids. The measurements show a relationship between slug flow characteristics and particle attributes, showing a nonlinear behavior influenced by both particle size and concentration, potentially explained via turbulence modulation. The particle size relative to the turbulent eddy size can either promote or damp the turbulence intensity, with impact on the peak velocity of the flow, and consequences in the elongated bubble velocity. In the case of lower mixture velocities and higher liquid loadings, particles also influence the slug flow formation.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Gas hydrates; Multiphase flow; Size/concentration; Slug flow; Solid particles